A VICTIMOLOGICAL PERSPECTIVE ON CHILD VICTIMS OF OBSCENE ACTS - Mohammad Ali Fikri; Nashriana (Fakultas Hukum Universitas Sriwijaya, 2026)
Abstract: Victimology of children as victims of sexual crimes, by identifying the problem of the Victimological Perspective of the Crime of Abuse Against Children where this problem is still a very important issue for the Government, especially for parents. The research method used by this researcher is normative descriptive legal research. Based on what is stipulated in Law Number 35 of 2014 concerning Child Protection, there are still many child victims who do not get protection from a legal perspective. The results showed that the causes of the crime of child molestation can be seen from economic factors, environmental factors and the lack of parental supervision which causes children to experience various mental disorders for the child's future.